Zinc oxide nanoparticles produced by Zingiber officinale ameliorates acute toxoplasmosis-induced pathological and biochemical alterations and reduced parasite burden in mice model. - Asmaa M El-Kady; Abeer S Hassan; Khalil Mohamed; Mashael S Alfaifi; Hayam Elshazly; Zaenah Zuhair Alamri; Majed H Wakid; Hattan S Gattan; Sarah A Altwaim; Wafa Abdullah I Al-Megrin; Salwa Younis (Public Library of Science (PLoS), 2023)
Background Although, approximately 30% of the world's population is estimated to be infected with Toxoplasma gondii (T. gondii) with serious manifestations in immunocompromised patients and pregnant females, the available treatment options for toxoplasmosis are limited with serious side effects. Therefore, it is of great importance to identify novel potent, well tolerated candidates for treatment of toxoplasmosis. The present study aimed to evaluate the effect of Zinc oxide nanoparticles (ZnO NPs) synthesized using Zingiber officinale against acute toxoplasmosis in experimentally infected mice. Methods The ethanolic extract of ginger was used to prepare ZnO NPs. The produced ZnO NPs were characterized in terms of structure and morphology using Fourier Transformed Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), UV- spectroscopy and scanning electron microscopy (SEM). The prepared formula was used in treatment of T. gondii RH virulent strain. Forty animals were divided into four groups, with ten mice per group. The first group was the uninfected, control group. The second group was infected but untreated. The third and the fourth groups received ZnO NPs and Spiramycin orally in a dose of 10 mg/kg and 200 mg/kg/day respectively. The effect of the used formulas on the animals survival rate, parasite burden, liver enzymes -including Alanine transaminase (ALT) and aspartate transaminase (AST)-, nitric oxide (NO) and Catalase antioxidant enzyme (CAT) activity was measured. Moreover, the effect of treatment on histopathological alterations associated with toxoplasmosis was examined. Results Mice treated with ZnO NPs showed the longest survival time with significant reduction in the parasite load in the livers and peritoneal fluids of the same group. Moreover, ZnO NPs treatment was associated with a significant reduction in the level of liver enzymes (ALT, AST) and NO and a significant increase in the antioxidant activity of CAT enzyme. SEM examination of tachyzoites from the peritoneal fluid showed marked distortion of T. gondii tachyzoites isolated from mice treated with ZnO NPs in comparison to untreated group. T. gondii induced histopathological alterations in the liver and brain were reversed by ZnO NPs treatment with restoration of normal tissue morphology. Conclusion The produced formula showed a good therapeutic potential in treatment of murine toxoplasmosis as demonstrated by prolonged survival rate, reduced parasite burden, improved T. gondii associated liver injury and histopathological alterations. Thus, we assume that the protective effect observed in the current research is attributed to the antioxidant capability of NPs. Based on the results obtained from the current work, we suggest greenly produced ZnO NPs as a chemotherapeutic agent with good therapeutic potential and high levels of safety in the treatment of toxoplasmosis.